TikTok and Islamic State of Iraq and Syiria (ISIS) Propaganda - Shofia Rakhma; Pujo Widodo; Agus H. Sulistyono Reksoprodjo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
ISIS emphasizes the importance of winning the hearts and minds of individuals in their operational strategy. Their objective is to draw sympathizers, propagate their objectives and ideology, and allocate substantial resources. They have utilized TikTok as a platform to garner attention and disseminate propaganda, with the aim of promoting their organization and recruiting new terrorists.This study employed qualitative research methods, with data gathered through interviews and documentation. The findings indicate that ISIS’s propaganda on TikTok poses a significant threat to Indonesia’s national security. It has the potential to sway the younger generation towards supporting extremist and terrorist ideologies. ISIS employs a variety of techniques to propagate their message. These include the use of the keyword “dawlah”, displaying the ISIS flag with stickers, using nasheed or song lyrics, creating sarcastic memes, and advocating for jihad, death, and suicide. They also leverage TikTok’s features, such as filters and hearts, to promote their organization. ISIS produces video content that glorifies its militants, accompanied by ISIS songs that are rhythmic, lyrical, and delivered in a catchy manner. They also display videos showing corpses being paraded on the streets, ISIS militants armed with weapons, and videos themed “Jihad Lover” targeting young women. The aim of these contents is to incite hatred, division, and social mistrust towards the state, government, and legitimate leaders. This is an academic English paraphrase of the original text.